Characteristics of Bedayan Retna Dumilah Dance Motions Created by S. Ngaliman Condropangrawit - Herlinah, Herlinah (Harmonia: Journal of Arts Research and Education, 2019)
The purpose of this study is to describe the characteristics of Bedayan Retna Dumilah dance motions created by S. Ngaliman Condropangrawit. This research uses descriptive qualitative method. The research subjects are three figures who are familiar with the Bedayan Retna Dumilah dance. Data collection techniques used the method of observation, in-depth interviews, and documentation study. Data analysis techniques were conducted through the stages of data reduction, data description, and conclusion drawing. Data validation was conducted through the triangulation of sources. The results show that the Bedayan Retna Dumilah dance is a Surakarta style traditional dance that combines the feeling of classical dance motions of the Surakarta Kasunanan Palace with the sense of motion of Kemlayan village artists. The main idea of the Bedayan Retna Dumilah dance was inspired by Bedaya Bedhah Madiun. The Bedayan Retna Dumilah dance range of motions was taken from the Srimpi Sangupati, the Srimpi Gondokusuma, and the Srimpi Anglirmendung dances range of motions. The characteristics of the range of motions found in the Bedayan Retna Dumilah dance are: 1) Sekaran Lara Retna Dumilah which is a development of the sekaran laras sawit; 2) the standing style sekaran lenggut which is a development of the lenggut on sembahan trapsila and sembahan jengkeng. The two characteristics of the range of motion are not found in the other dances.